Associations between circulating inflammatory markers, diabetes type and complications in youth. Issue 8 (2nd October 2019) - Aulich, Juliane; Cho, Yoon Hi; Januszewski, Andrzej S.; Craig, Maria E.; Selvadurai, Hiran; Wiegand, Susanna; Jenkins, Alicia J.; Donaghue, Kim C.
Abstract: Background: Inflammation is implicated in the pathogenesis of diabetes and its complications in adults. Little is known about the relative contribution of inflammation in common types of diabetes in youth: type 1 diabetes (T1D), type 2 diabetes (T2D), and cystic fibrosis‐related diabetes (CFRD). This study investigates inflammatory markers by diabetes type and complication status, and assesses indicators of inflammation and complications. Methods: A cross‐sectional study of 134 T1D, 32 T2D, 32 CFRD and 48 subjects without diabetes (including 11 with CF and normal glucose tolerance) was undertaken. Inflammation was assessed by sE‐selectin by ELISA, hsCRP by turbidimetry, WCC and ESR. Nephropathy was defined by albuminuria, autonomic neuropathy by heart rate variability, and peripheral neuropathy by vibration and thermal threshold testing and retinopathy by seven‐field stereoscopic fundus photography. Descriptive statistics, parametric and non‐parametric ANOVA and regression analyses were performed, with significance at P < .05. Results: Of 198 diabetic participants; 49% female, mean (SD) age, median diabetes duration and median HbA1c were 16 (2.5) and 6 (3–9) years, and 8.1 (6.9‐9.3)%, respectively. All inflammatory markers were lower in T1D than in other diabetes groups ( P < .05) but higher than in non‐diabetic controls. T2D (n = 32) and CFRD (n = 32) subjects had comparable elevated levels of inflammation. Body mass index (BMI) was a strong independent explanatory variable of inflammation. In multivariate analysis, hsCRP and ESR were associated with complications in addition to HbA1c, BMI, and diastolic BP. Conclusions: Circulating inflammatory markers are elevated in adolescents with diabetes, being higher and comparable in T2D and CFRD than in T1D. Inflammation is independently associated with diabetes complications, consistent with inflammation driving vascular pathology in diabetes.